1996
DOI: 10.1002/chin.199627150
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Synthesis of Some Novel Pyrazoline and Cyanopyridine Derivatives as Antimicrobial Agents.

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 100 leading journals. To access a ChemInform Abstract of an article which was published elsewhere, please select a “Full Text” option. The original article is trackable via the “References” option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…Replacement of the methoxy group (26 and 28) with either F (30) or Cl (31) resulted in a drop in the antioxidant activity, which suggested that electron-donating groups are favored at positions 2 on the phenyl ring. A similar phenomenon was observed in the dihydropyrazole series (32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46). Compound 43 was found to have an IC 50 of 6 µg/mL and was the most potent in this series.…”
Section: Antioxidant Activitysupporting
confidence: 76%
See 2 more Smart Citations
“…Replacement of the methoxy group (26 and 28) with either F (30) or Cl (31) resulted in a drop in the antioxidant activity, which suggested that electron-donating groups are favored at positions 2 on the phenyl ring. A similar phenomenon was observed in the dihydropyrazole series (32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46). Compound 43 was found to have an IC 50 of 6 µg/mL and was the most potent in this series.…”
Section: Antioxidant Activitysupporting
confidence: 76%
“…The crude precipitate was recrystallized using chloroform to afford chalcones 17-31. The target dihydropyrazoles (32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46) were obtained by treating the synthesized chalcones with semicarbazide in a catalytic amount of pyridine and purified using silica gel column chromatography.…”
Section: Chemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…Several pyrazoline derivatives possess important biological activities such as anti-inflammatory [2][3][4], antidepressant [5][6], antipyretic [7], antibacterial [8][9][10][11][12][13], antifungal [8,11,14] and antitumoral [15]. Over the years, the structure of pyrazoline [1,16] has received considerable attention.…”
Section: Introductionmentioning
confidence: 99%
“…Over the years, the chemistry of 1H-pyrazoles has received considerable attention [1,2]. It is worthy of note that substances containing a 1H-pyrazole moiety have been described as having potential therapeutic utility, such as antiinflammatory [3][4][5], antidepressant [6,7], antipyretic [8], antibacterial [9][10][11][12][13][14], antifungal [12,15] and antitumoral [16]. Of particular interest is the use of 1H-pyrazoles as synthetic intermediates for preparing cyclopropane [17][18][19] and pyrazole derivatives [1,[20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%